Iranian teachers’ and students’ preferences for correction of classroom oral errors: Opinions and responses - Farahani, Ali Akbar; Salajegheh, Soory (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
The aim of the present study was to investigate the teachers’ and students’ perceptions regarding the role they believe error correction plays in learning a new language. A questionnaire was administered to 429 Iranian foreign language students and 31 of their teachers. Data comparisons using the multivariate analysis of variance (MANOVA) showed agreement between teachers and students on most of the questions. However, there were some discrepancies between teachers and students specifically relating to the frequency for giving and receiving spoken error correction. Considering the danger of disagreements in teacher and student perceptions, it is significant for the teachers to identify their students’ preferences with respect to the factors considered to improve the language learning and attempt to manage the contrasts between student perspectives and pedagogical practice.